2022
DOI: 10.1007/s00382-022-06179-3
|View full text |Cite
|
Sign up to set email alerts
|

Investigating decadal variations of the seasonal predictability limit of sea surface temperature in the tropical Pacific

Abstract: El Niño and the Southern Oscillation (ENSO) have a worldwide impact on seasonal to yearly climate. However, there are decadal variations in the seasonal prediction skill of ENSO in dynamical and statistical models; in particular, ENSO prediction skill has declined since 2000. The shortcomings of models mean that it is very important to study ENSO seasonal predictability and its decadal variation using observational/reanalysis data. Here we quantitatively estimate the seasonal predictability limit (PL) of ENSO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…For example, many studies have shown decadal-scale variability in ENSO, and its predictability (e.g. Hou et al, 2022;Tang et al, 2008;Weisheimer et al, 2022;and references therein), and similarly for the EASM and WPSH (e.g. Li et al, 2016;Y.…”
Section: Discussionmentioning
confidence: 99%
“…For example, many studies have shown decadal-scale variability in ENSO, and its predictability (e.g. Hou et al, 2022;Tang et al, 2008;Weisheimer et al, 2022;and references therein), and similarly for the EASM and WPSH (e.g. Li et al, 2016;Y.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we applied the improved‐LDA method to identify the analogs. Numerous studies have successfully employed the NLLE method to investigate the predictability of atmospheric and oceanic systems (Ding et al., 2008; He et al., 2021; Hou et al., 2018; Hou, Li, Ding, et al, 2022; Li et al., 2018; Mengist & Seo, 2022).…”
Section: Methodsmentioning
confidence: 99%